Review of We Belong to Big Church: Caribbean Soundings and Stories in Anglicania - Anatol Allison Ferguson (Theological Librarianship, 2023)
We Belong to Big Church: Caribbean Soundings and Stories in Anglicania provides a rare insight into the cross-cultural dynamics of Afro-Anglicanism in the Caribbean and in North America. The historic fictional religious narratives of the first section give a voice to the ecclesial and cultural adjustments of the Anglican Caribbean Diaspora in America. The second section is a compilation of the author’s sermons, addresses, and lectures that engage issues of multiculturalism, inclusion, and racism as a call to stimulate further conversations on a proposed way forward in the Ecclesia Anglica. As the Professor of Theology at Howard University School of Divinity, Kortright Davis’ book is a creative and educative gem that fills the void of Afro-Caribbean literature and is a good starting place for navigating the conversations on cultural diversity.